The Intervention of Nano-targeted Drugs & Angioplastryin Treatment and Prevention of Vascular Restenosis and its Influence on Monocyte Chemotactic Protein-1 in Lower Extremity Angiopathy: Nano-targeted Drugs and Angioplastry for Vascular Restenosis - Ji, Kun; Zhang, Yaming; Huang, Daojing (Cellular and Molecular Biology, 2022)
It was to make use of the nano-targeted drugs and angioplastry to treat and prevent the vascular restenosis and analyze its influence on monocyte chemotactic protein 1 (MCP-1) of lower extremity angiopathy (LEA) patients since the patients with diabetic lower extremity angiopathy may be easily infected with vascular restenosis. In this article, the dexamethasone nano drugs were firstly prepared. After that, its related physical and chemical properties were tested, then, dexamethasone nano drugs were applied in treating patients with diabetic lower extremity angiopathy. The results showed that the prepared dexamethasone nanoparticles’ encapsulation rate attained 99.2%. The laser light scattering experiment manifested that the particle size of the nanoparticles ranged from 200 to 300nm, and the average particle size was 258nm. The MCP-1 of the control group, conventional group, and observation group were 33.28±1.93 µg/mL, 78.27±9.73 µg/mL, and 75.29±8.99 µg/mL, respectively. The MCP-1 values of the conventional and observation groups were higher than that of the control group, and there was a notable difference (P<0.05). After interventional treatment, the MCP-1 level of the conventional group was 57.82±5.82 µg/mL, and that of the observation group was 41.93±6.92 µg/mL. The MCP-1 level of the group which received the treatment of nano-targeted drugs and angioplastry was superior to that of the conventional group which received the traditional operation, and there was a notable difference (P<0.05). In conclusion, MCP-1 is one of the major causes of lower extremity angiopathy. The nano-targeted drugs and angioplastry can raise the expression level of MCP-1 in patients with lower extremity angiopathy. The experimental results had a high application value and the nano-targeted drugs & angioplastry can be promoted clinically.